Impact of Remineralization Profile Shape on the Air‐Sea Carbon Balance. Issue 7 (9th April 2021) - Lauderdale, Jonathan Maitland; Cael, B. B.
Abstract: The ocean's "biological pump" significantly modulates atmospheric carbon dioxide levels. However, the complexity and variability of processes involved introduces uncertainty in interpretation of transient observations and future climate projections. Much research has focused on "parametric uncertainty, " particularly determining the exponent(s) of a power‐law relationship of sinking particle flux with depth. Varying this relationship's functional form introduces additional "structural uncertainty." We use an ocean biogeochemistry model substituting six alternative remineralization profiles fit to a reference power‐law curve, to systematically characterize structural uncertainty, which, in atmospheric pCO2 terms, is roughly 50% of parametric uncertainty associated with varying the power‐law exponent within its plausible global range, and similar to uncertainty associated with regional variation in power‐law exponents. The substantial contribution of structural uncertainty to total uncertainty highlights the need to improve characterization of biological pump processes, and compare the performance of different profiles within Earth System Models to obtain better constrained climate projections. Plain Language Summary: The ocean's "biological pump" regulates atmospheric carbon dioxide levels and climate by transferring organic carbon produced at the surface by phytoplankton to the ocean interior via "marine snow, " where the organic carbon is consumed and respired by microbes. This surface to deep transport is usually described by a power‐law relationship of sinking particle concentration with depth. Uncertainty in biological pump strength can be related to different variable values ("parametric" uncertainty) or the underlying equations ("structural" uncertainty) that describe organic matter export. We evaluate structural uncertainty using an ocean biogeochemistry model by systematically substituting six alternative remineralization profiles fit to a reference power‐law curve. Structural uncertainty makes a substantial contribution, about one‐third in atmospheric pCO2 terms, to total uncertainty of the biological pump, highlighting the importance of improving biological pump characterization from observations and its mechanistic inclusion in climate models. Key Points: Six alternative flux profiles fit to a Martin Curve yield large differences in atmospheric carbon Structural uncertainty comprises one‐third of total uncertainty in the ocean's biological pump Varying particle attenuation with depth may account for half of the biological pump's overall carbon drawdown